Questions & Answers

Question

Answers

Answer

Verified

161.1k+ views

Hint: Simplify the denominator which is an infinite function and differentiate by applying product rule.

Here \[y\] is an infinite function. By observation, we can see the pattern that \[\sin x\] and \[\cos x\]appear alternatingly and hence, we can write \[y\] as

\[y=\dfrac{\sin x}{1+\dfrac{\cos x}{1+y}}\]

\[\Rightarrow y=\dfrac{\sin x}{\dfrac{1+y+\cos x}{1+y}}\]

\[\Rightarrow y=\dfrac{\sin x(1+y)}{1+y+\cos x}\]

\[\Rightarrow y(1+y+\cos x)=\sin x(1+y)\]

Differentiating both sides with respect to\[x\], we get,

\[(1+y+\cos x).\dfrac{dy}{dx}+y(1+\dfrac{dy}{dx}-\sin x)=(1+y)\cos x+\sin x(\dfrac{dy}{dx})\]

\[\Rightarrow (1+y+\cos x).\dfrac{dy}{dx}+y+y\dfrac{dy}{dx}-y\sin x=(1+y)\cos x+\sin x(\dfrac{dy}{dx})\]

Taking all the terms with \[\dfrac{dy}{dx}\]to one side and other terms to the other side, we get,

\[\Rightarrow (1+y+\cos x).\dfrac{dy}{dx}+y\dfrac{dy}{dx}-\sin x(\dfrac{dy}{dx})=(1+y)\cos x+y\sin x-y\]

\[\Rightarrow (1+y+\cos x-\sin x+y).\dfrac{dy}{dx}=(1+y)\cos x+y\sin x-y\]

\[\Rightarrow \dfrac{dy}{dx}=\dfrac{y(cosx+\sin x-1)+\cos x}{1+2y+\cos x-\sin x}\]

Note: Generally students make a mistake of writing \[\dfrac{\sin x}{1+\dfrac{\cos }{1+\dfrac{sinx}{1+\cos x.....}}}\] as \[\dfrac{\sin x}{\dfrac{1+\cos x}{y}}\]which is wrong as the repetition starts after the addition of \[1\] in the denominator i.e. \[\dfrac{\sin x}{\dfrac{1+\cos x}{1+y}}\].

Here \[y\] is an infinite function. By observation, we can see the pattern that \[\sin x\] and \[\cos x\]appear alternatingly and hence, we can write \[y\] as

\[y=\dfrac{\sin x}{1+\dfrac{\cos x}{1+y}}\]

\[\Rightarrow y=\dfrac{\sin x}{\dfrac{1+y+\cos x}{1+y}}\]

\[\Rightarrow y=\dfrac{\sin x(1+y)}{1+y+\cos x}\]

\[\Rightarrow y(1+y+\cos x)=\sin x(1+y)\]

Differentiating both sides with respect to\[x\], we get,

\[(1+y+\cos x).\dfrac{dy}{dx}+y(1+\dfrac{dy}{dx}-\sin x)=(1+y)\cos x+\sin x(\dfrac{dy}{dx})\]

\[\Rightarrow (1+y+\cos x).\dfrac{dy}{dx}+y+y\dfrac{dy}{dx}-y\sin x=(1+y)\cos x+\sin x(\dfrac{dy}{dx})\]

Taking all the terms with \[\dfrac{dy}{dx}\]to one side and other terms to the other side, we get,

\[\Rightarrow (1+y+\cos x).\dfrac{dy}{dx}+y\dfrac{dy}{dx}-\sin x(\dfrac{dy}{dx})=(1+y)\cos x+y\sin x-y\]

\[\Rightarrow (1+y+\cos x-\sin x+y).\dfrac{dy}{dx}=(1+y)\cos x+y\sin x-y\]

\[\Rightarrow \dfrac{dy}{dx}=\dfrac{y(cosx+\sin x-1)+\cos x}{1+2y+\cos x-\sin x}\]

Note: Generally students make a mistake of writing \[\dfrac{\sin x}{1+\dfrac{\cos }{1+\dfrac{sinx}{1+\cos x.....}}}\] as \[\dfrac{\sin x}{\dfrac{1+\cos x}{y}}\]which is wrong as the repetition starts after the addition of \[1\] in the denominator i.e. \[\dfrac{\sin x}{\dfrac{1+\cos x}{1+y}}\].